2017
DOI: 10.1038/s41598-017-11904-8
|View full text |Cite
|
Sign up to set email alerts
|

MiR-503 modulates epithelial-mesenchymal transition in silica-induced pulmonary fibrosis by targeting PI3K p85 and is sponged by lncRNA MALAT1

Abstract: Silicosis is a kind of chronic, progressive and incurable lung fibrotic diseases with largely unknown and complex pathogenesis and molecular mechanisms. Mounting evidence suggests that microRNAs (miRNAs, miRs) are involved in the pathogenesis of silicosis. Our previous study based on miRNA microarray had shown that the expression levels of miR-503 were down-regulated in mouse lung tissues of silica-induced pulmonary fibrosis. Here, we validated the decreased expression of miR-503 in the fibrotic mouse lung tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 61 publications
5
87
0
Order By: Relevance
“…Chen et al (32) found that up-regulation of lncRNA in colorectal cancer liver metastasis (UICLM) promoted colorectal cancer metastasis by acting as a ceRNA of miR-215. Yan et al (33) reported that lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) promoted EMT by binding to miR503, which then resulted in lung fibrosis. A recent study by Liu et al (34) demonstrated that lncRNA PCF contributed to lung fibrosis through promotion of activated epithelial cell proliferation by binding to miR-344a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (32) found that up-regulation of lncRNA in colorectal cancer liver metastasis (UICLM) promoted colorectal cancer metastasis by acting as a ceRNA of miR-215. Yan et al (33) reported that lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) promoted EMT by binding to miR503, which then resulted in lung fibrosis. A recent study by Liu et al (34) demonstrated that lncRNA PCF contributed to lung fibrosis through promotion of activated epithelial cell proliferation by binding to miR-344a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…22 MALAT1 inhibited infiltration of inflammatory CD45+ cells partly via sponging miR-503. 41 The exosomes containing MALAT1 released from Ox-LDL-treated ECs could promote the M2 macrophage and IL-10 production and inhibit the M1 macrophage and IL-12 production. 51 High glucose also induces inflammatory cytokine such as IL-6 and tumor necrosis factor α (TNF-α) through MALAT1 mediated upregulation of serum amyloid antigen 3 (SAA3) in HUVECs.…”
Section: The Malat1 and Inflammationmentioning
confidence: 97%
“…MALAT1 could reverse the ox‐LDL induced inflammation by sponging miR‐155, thereby increasing the level of SOCS1 . MALAT1 inhibited infiltration of inflammatory CD45+ cells partly via sponging miR‐503 . The exosomes containing MALAT1 released from Ox‐LDL‐treated ECs could promote the M2 macrophage and IL‐10 production and inhibit the M1 macrophage and IL‐12 production .…”
Section: Malat1 and Vascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known about miRNA functions in IPF; much of the functional data has been inferred from chemically induced mouse IPF models. In the lungs of mouse IPF models, miR-21, miR-9, and miR-155 were increased [19,21,30], and miR-26, miR-101, miR-139, miR-200, miR-326, miR-489, miR-503, and miR-708 were decreased [24,[31][32][33][34][35][36][37]. Furthermore, miR-21 expression was increased in myofibroblasts from IPF lungs, and its inhibition in mouse IPF models attenuated the disease severity [19].…”
Section: Ipf and Mirnasmentioning
confidence: 99%